2023
DOI: 10.1007/jhep11(2023)155
|View full text |Cite
|
Sign up to set email alerts
|

Scaling similarities and quasinormal modes of D0 black hole solutions

Anna Biggs,
Juan Maldacena

Abstract: We study the gravity solution dual to the D0 brane quantum mechanics, or BFSS matrix model, in the ’t Hooft limit.The classical physics described by this gravity solution is invariant under a scaling transformation, which changes the action with a specific critical exponent, sometimes called the hyperscaling violating exponent. We present an argument for this critical exponent from the matrix model side, which leads to an explanation for the peculiar temperature dependence of the entropy in this theory, S ∝ T9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…This is conceptually equivalent to considering off-diagonal elements E| Tr M |E . A hope is that one could match to gravity expectations, like the quasi-normal modes in [30].…”
Section: Jhep06(2023)038mentioning
confidence: 95%
“…This is conceptually equivalent to considering off-diagonal elements E| Tr M |E . A hope is that one could match to gravity expectations, like the quasi-normal modes in [30].…”
Section: Jhep06(2023)038mentioning
confidence: 95%
“…• It has recently been suggested that quasinormal modes can serve as a signature for having successfully simulated (quantum) gravity on a (quantum) computer [76,77].…”
Section: Jhep12(2023)187mentioning
confidence: 99%